1999
DOI: 10.1016/s0092-8674(00)80788-6
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Cyclin D1 Deficiency by Knockin Cyclin E

Abstract: D-type cyclins and cyclin E represent two very distinct classes of mammalian G1 cyclins. We have generated a mouse strain in which the coding sequences of the cyclin D1 gene (Ccnd1) have been deleted and replaced by those of human cyclin E (CCNE). In the tissues and cells of these mice, the expression pattern of human cyclin E faithfully reproduces that normally associated with mouse cyclin D1. The replacement of cyclin D1 with cyclin E rescues all phenotypic manifestations of cyclin D1 deficiency and restores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
215
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(236 citation statements)
references
References 23 publications
18
215
1
2
Order By: Relevance
“…Interestingly, this altered response was not due to the massive deregulation of RB/E2F-target gene expression, but rather to perturbations that are known to directly influence CDK2 function. These findings are consistent with studies from genetic models, wherein the utilization of a particular CDK can be substituted by another (Geng et al, 1999). Seemingly, these controls are already somewhat compromised in MCF-10A cells, and this finding may in fact contribute to the pivotal requirement for Rb in eliciting acute cell-cycle inhibition in this model.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, this altered response was not due to the massive deregulation of RB/E2F-target gene expression, but rather to perturbations that are known to directly influence CDK2 function. These findings are consistent with studies from genetic models, wherein the utilization of a particular CDK can be substituted by another (Geng et al, 1999). Seemingly, these controls are already somewhat compromised in MCF-10A cells, and this finding may in fact contribute to the pivotal requirement for Rb in eliciting acute cell-cycle inhibition in this model.…”
Section: Discussionsupporting
confidence: 88%
“…Future study is needed to explore whether the other major downstream property of cyclin D1/CDK4, e.g. sequestering the CDK inhibitor p27 Kip1 to trigger cyclin E-initiated Rb-independent S phase entry (Geng et al, 1999;Perez-Roger et al, 1999;Donnellan and Chetty, 1999), is associated with novel tumorigenic mechanisms caused by ampli®ed PIK3CA in cervical cancer development. Not mutually exclusive are the possibilities that, in cervical tumorigenesis, increased PIK3CA and elevated PI 3-kinase activity contribute to other AKT-involved growth-promoting pathways or antiapoptotic signal.…”
Section: Resultsmentioning
confidence: 99%
“…In our studies, we were unable to detect any difference in cyclin D2 and D3 expression between CERM and CERM D1À/À mammary glands. It has been shown that the genetic replacement of cyclin D1 with human cyclin E in transgenic mice rescues the cyclin D1-deficient phenotype (Geng et al, 1999). It is important to note that in these knock-in mice, the expression of human cyclin E is driven by the cyclin D1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 and E are considered weak oncogenes since their overexpression results in the formation of long-latency mammary adenocarcinomas (Sutherland and Musgrove, 2004). In addition, these proteins seem to have redundant functions in mammary gland development since the cyclin D1 knockout phenotype can be rescued by genetic replacement with cyclin E (Geng et al, 1999). Previous studies showed that cyclin E overexpression causes DNA damage and checkpoint activation (Spruck et al, 1999;Ekholm-Reed et al, 2004;Bartkova et al, 2005;Minella et al, 2007).…”
Section: Introductionmentioning
confidence: 99%